The influence of corporate market power on health: exploring the structure-conduct-performance model from a public health perspective - Benjamin Wood; Owain Williams; Phil Baker; Vijaya Nagarajan; Gary Sacks (BMC, 2021)
Abstract Background The detrimental impact of dominant corporations active in health-harming commodity industries is well recognised. However, to date, existing analyses of the ways in which corporations influence health have paid limited attention to corporate market power. Accordingly, the public health implications of concentrated market structures, the use of anti-competitive market strategies, and the ways in which market power mediates the allocation and distribution of resources via market systems, remain relatively unexplored. To address this gap, this paper aimed to identify and explore key literature that could inform a comprehensive framework to examine corporate market power from a public health perspective. The ultra-processed food (UPF) industry was used to provide illustrative examples. Methods A scoping review of a diverse range of literature, including Industrial Organization, welfare economics, global political economy and antitrust policy, was conducted to identify important concepts and metrics that could be drawn upon within the field of public health to understand and explore market power. The Structure-Conduct-Performance (SCP) model, a guiding principle of antitrust policy and the regulation of market power, was used as an organising framework. Results We described each of the components of the traditional SCP model and how they have historically been used to assess market power through examining the interrelations between the structure of industries and markets, the conduct of dominant firms, and the overall ability of markets and firms to efficiently allocate and distribute the scarce resources. Conclusion We argue that the SCP model is well-placed to broaden public health research into the ways in which corporations influence health. In addition, the development of a comprehensive framework based on the key findings of this paper could help the public health community to better engage with a set of policy and regulatory tools that have the potential to curb the concentration of corporate power for the betterment of population health.